Development of eco-friendly microwaved chitosan-based nanocomposite membrane for efficient capturing of cationic dyes from aqueous solution: permeability and fouling studies - Katibi, Kamil Kayode; Shitu, Ibrahim Garba; Othman, Siti Hajar; Md Yunos, Khairul Faezah; Ismail, Ahmad Fauzi; Noorisma KhairulAqmar, Noordinie Afina; Ilias, Hanis Masyithah (Springer Nature, 2024)
Removing deleterious cationic dyes from wastewater is crucial due to their persistence, toxicity, and harmful effects on public health and ecosystems. In this study, microwaved chitosan nanoparticles (MWCNP) were synthesized and characterized using transmission electron microscopy and Fourier-transform infrared spectroscopy to assess their size and functional groups. Then, nascent polyvinylidene fluoride-polyethylene glycol membrane and composite membranes were fabricated with varying MWCNP concentrations (0.3–1.0 wt.%) through the non-solvent phase inversion (NIPs) technique. The resulting membranes underwent analysis for porosity, contact angle, tensile strength, energy dispersive X-ray (EDX), field emission scanning electron microscopy (FESEM), permeate flux, surface zeta potential, fouling resistance, and dye removal. Composite membranes outperformed nascent ones, with the 0.7 wt.% MWCNP composite membrane exhibiting the best performance, having a contact angle of 49.8°, a zeta potential of − 47.4 mV, tensile strength of 2.9 MPa, porosity of 83.7%, methylene blue removal of 96.7%, and permeate flux of 125.3 L.m−2.h−1. The 0.7 wt.% MWCNP composite membrane also showed enhanced antifouling properties after three filtration cycles with an FRR of 80.7% and an RFR of 16.2%. These results demonstrate the efficiency of MWCNP-containing membranes, making them suitable for textile wastewater treatment. © Qatar University and Springer Nature Switzerland AG 2024.